Prison Unhealthy Lifestyle and Poor Mental Health of Older Persons—A Qualitative Study - Pageau, Félix; Cornaz, Corinne Devaud; Gothuey, Isabelle; Seaward, Helene; Wangmo, Tenzin; Elger, Bernice S. (Frontiers in Psychiatry, 2021)
Background: Mental healthcare and lifestyle habits in prison, especially for older individuals has been shown to be suboptimal. Most psychiatric conditions left untreated worsen food choices, physical inactivity and substance abuse. In turn, bad habits lead to poorer mental health. Methods: To comprehensively illustrate this downward spiraling, we completed a thorough analysis of data obtained through semi-structured qualitative interviews. 50 interviews of ageing incarcerated people were included in this article. They were analyzed following a classical six-stepped thematic analysis. Results: According to our participants, sports are not well-adapted to ageing individuals, nor to people with medical conditions. Prison is even more unadapt for those who both are ageing and have medical conditions. Also, food served is less than optimal. According to our interviews, the older imprisoned individual often does not have access to food adapted to his/her medical conditions. Sport is maladapted for older incarcerated individual and mostly tailored for younger ones. Finally, boredom and lack of responsibility hinder change toward a better lifestyle for older adults in prison. Conclusion: Our paper shows why prison environmental modifications are needed to help older adults with their lifestyle habits. It also exposes an original way to see the relationship between mental health and lifestyle habits.